Protective Effect of Tea Polyphenol Ophthalmic Gel on Lens Epithelial Cells in Rabbits with Silicone Oil Tamponade after Vitrectomy. (19th November 2014) - Ma, Xianzhen; Guo, Dadong; Bi, Hongsheng; Xie, Xiaofeng; Guo, Junguo; Cui, Yan
Abstract : Purpose . The aim of this study was to investigate the effect of tea polyphenols (TP) ophthalmic gel on lens epithelial cells (LECs) in rabbits with silicone oil tamponade after vitrectomy. Methods . In this study, unilateral vitrectomy with silicone oil tamponade was performed using 2-month-old New Zealand white rabbits ( n = 72); meanwhile, age-matched nonoperated rabbits ( n = 18) were used as controls. The TP ophthalmic gel was administered topically in the surgical eyes till they were sacrificed. On days 45 and 90 after operation, the levels of reactive oxygen species (ROS), mitochondrial membrane potential (ΔΨm), and apoptosis of LECs were analyzed, respectively. Meanwhile, caspase-3 mRNA and protein levels were also determined. Results . The results indicate that the levels of ROS and apoptosis were elevated for LECs in rabbits after operation, whereas ΔΨm was decreased. Caspase-3 was apparently increased at both mRNA and protein levels. Treatment of TP ophthalmic gel could reduce the generation of ROS, maintain ΔΨm, inhibit the overexpression of caspase-3, and thus decrease the apoptosis of LECs of rabbits after operation. Conclusions . TP ophthalmic gel can efficiently inhibit caspase-3 overexpression, reduce the apoptosis of LECs, and prevent LECs from damage. Our result provides a new approach to prevent the development of complicated cataract after vitrectomy.